Atypical rash, a diagnostic challenge in clinical practice: A Case Report from Bolivia - Paz-Román, Carlos Alberto; Auza-Santivañez, Jhossmar Cristians; Fuentes Luzcuber, Paola Nielsen; Rivero Castedo, Leonel; Kubatz La Madrid, Mildred Ericka; Robles-Nina, Sara Milca; Salvatierra Rocha, Carmen Julia; Márquez Molina, Jorge (Salud Integral y Comunitaria, 2026)
Hand-foot-and-mouth disease, commonly caused by Coxsackievirus A16, can manifest in atypical and severe forms associated with the CVA6 serotype, termed "eczema coxsackium," which may mimic serious pathologies. This report describes the case of a 10-year-old boy with a diffuse maculopapular rash, targetoid and bullous lesions, and systemic compromise, initially diagnosed as erythema multiforme major. The discussion focuses on the differential diagnostic challenge with eczema herpeticum, highlighting that despite the alarming clinical presentation, etiological confirmation via PCR for CVA6 was crucial to rule out other infections, discontinue unnecessary acyclovir, and focus treatment on supportive care, leading to a favorable outcome. In conclusion, eczema coxsackium due to CVA6 should be considered in severe vesiculobullous rashes, with PCR being essential for an accurate diagnosis and proper management, as its prognosis is generally benign.